WAá¸¤DAT AL-WUJÃD DALAM ALQURAN - Nasution, ismail fahmi arrauf nasution (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2016)
Waá¸¥dat al-wujÃ»d is a doctrine that believes in the ultimate form of God. While the universe is believed as a shadow that totally depends on the Creator (á¸¤aqq TaâÃ¢lÃ¢). Waá¸¥dat al-wujÃ»d is one of the most inciting topics debated by Muslim scholars in the middle time of Islam. The opponents of waá¸¥dat al-wujÃ»d has used to accuse it as heresy. They consider waá¸¥dat al-wujÃ»d as theologically rooted from Zoroastrianism, Hinduism, Platonism and Neoplatonism. The opponents of waá¸¥dat al-wujÃ»d generally come from âliteral-mindedâ theologians. They tend to understand the Qurâan and á¸¥adÃ®th in its outward meaning. Whereas the inner meaning has abundantly been contained in the Qurâan. This paper is an effort to analyze some verses of the Qurâan by using taâwÃ®l (esoteric analysis) and to some extent is a reflection on Syamsuddin al-Sumatraniâs teaching. In the end, this paper argues that although literally term of waá¸¥dat al-wujÃ»d does not exist in the Qurâan, however, the analysis shows that the teaching of waá¸¥dat al-wujÃ»d is definitely rooted in the Quran.